Energy conservation project funding in commercial building: an expenditure or investment? - Shaikh Shamser Ali; Ruchi Tyagi; Ragini Chauhan (Institute of Advanced Engineering and Science, 2019)
Energy conservation is an unnecessary expenditure and considered as a less important operational activity in many third world countries, particularly in India. The review of literature on the energy conservation project funding identifies that unclear management vision and policy for energy conservation is one of the reason for its back seat. Energy Conservation is supposed to be a top-down approach, in reality, a procurement manager is obliged to buy based on L1 policy (Lowest quoted price). Most of the Energy Conservation Measures (ECM) are not available at lowest quoted price. Therefore, Energy Conservation Measures (ECM) turn out to be a document formality rather than practice. The paper highlights the need for a paradigm shift on Energy conservation project from an expenditure to an investment. The Energy Conservation Project is an investment that will continue to give a return as long as the equipment is in operation or the facility is functional. This calls for amendments in Energy Policies and Project Guidelines for swift that there are no conflicts between the departments for implementing the energy conservation projects.